One Drop: Lab on a Chip - Richards, Megan; Brungardt, Kaley; Schuette, Kendra (Kansas State University. K-State Libraries, 2017)
Lab on a chip devices are currently being studied to aid in blood based diagnostic assaytests for personalized medicine applications. These biosensors are appealingdue to their low cost, simplicity of use, and quick feedback of results. Thegoal of team One Drop was to design a chip that simplifies the diagnosis ofbreast and ovarian cancer by searching for certain antigens in thebloodstream. The main objective for this semester has been to design amicrofluidic lab on a chip device that will mix blood and reagentstreams to generate turbulent flows within a fluidic chamber using noexternal forces. The resulting fluid mixture will settle within the device for further analysis. One Drop was able to prototype four differentmicrofluidic flow designs in SolidWorks for further simulation testing inCOMSOL multiphysics modeling with the aid of a theoretical analysis foranalyzing fluid flow properties. One design was selected due to its highdiffusive capability for efficient mixing of blood and reagent streams. Eachdesign was compared through qualitative analysis, a simple COMSOL simulation,and 3D printing capabilities.
Citation: Richards, M., Brungardt, K., & Schuette, K. (2017). One Drop: Lab on a Chip. Unpublished manuscript, Kansas State University, Manhattan, KS.
Kirmser Undergraduate Research Award - Group, honorable mention
Keywords: Lab on a chip; Biosensors; Blood-based diagnostic assay tests; Personalized medicine; Microfluidic device; Cancer diagnosis